Media Cerita Bergambar untuk Meningkatkan Keterampilan Menulis Puisi Anak: Picture Story Media to Improve Children's Poetry Writing Skills - Salamah, Evi Rizqi (Universitas Muhammadiyah Sidoarjo, 2017)
This research was conducted to improve the student’s ability in writing poetry which was caused by the lack of media that can stimulate students’ idea in teaching learning process so that the students’ ability in writing poetry was low. As a solution of that problem, the researcher used pictures story as mediain writing poetry. The researcher used classroom action research as a method. This study was conducted in two cycles and each cycle has four phases namely planning, implementation, observation, and reflection. The data collection was done by using observation, test and field notes. Qualitative and quantitative data analysis were conducted on the activities of teacher and students' test results, whereas the field notes was only as supporting data whichrecorded events during the learning process.Based on the data analysis showed that there were an increase in student learning outcomes and students were able to write good poetry. In addition, the barriers in teaching learning can be solved by giving sanctions and rewards.